Analisa Tingkat Kerusakan Struktur Kolom Terkena Tsunami - Samsunan Samsunan; Dian Febrianti (Universitas Teuku Umar, 2018)
Tsunami that occurred in Aceh at the end of 2004. has affected the buildings affected by the tsunami. The purpose of this study is to determine the condition of the current state and to analyze the level of damage to the structure of the column affected by the tsunami, one of which is the building of UPTD Bina Marga and Cipta Karya IV Meulaboh. This research is done by direct survey method to the field and conduct damage analysis of buildings based on Regulation of Minister of Public Works No.16/PRT/M/2010 on the technical guidance of periodic inspection of buildings. The result of the analysis is done classification level of damage according to the standard in Regulation of Minister of Public Works No.24/PRT/M/2008 about building maintenance and maintenance guidelines. The results showed that the column of the affected buildings had decreased the strength of the concrete, the condition of the column structure was all cracked and broken, most of the concrete blankets had been peeled, the main reinforcement conditions were corroded and some of the stirrup bones were broken. The result of concrete quality test is 114,41 kg/cm² lower than normal concrete strength. The results of the study and analysis that the affected columns on the buildings of UPTD Bina Marga and Cipta Karya Region IV Meulaboh are classified as heavy damage, the building of UPTD Bina Marga and Cipta Karya IV Meulaboh is not functional Keywords: Level of damage, Column Structure, UPTD Bina Marga Meulaboh and Cipta Karya IV Meulaboh region.